Activated CD4 + T lymphocyte is a potential biomarker for acute graft-vs.-host disease after hematopoietic stem cell transplantation in children with transfusion-dependent β-thalassemia - Huang, Ken; Luo, Jianming (Frontiers in Pediatrics, 2022)
Background: Acute graft-versus-host disease (aGVHD) is still one of the most common and life-threatening complications of allogeneic hematopoietic stem cell transplantation (HSCT). Whether or not the level of activated T lymphocytes rises before the onset of aGVHD is unknown. We explored the possibility of T lymphocytes as biomarkers for early prediction of aGVHD in children with transfusion-dependent β-thalassemia (TDTβ). Method: We retrospectively analyzed the characteristics of T lymphocyte subsets before and 14 days after HSCT in children with TDTβ who developed aGVHD. Data from 95 children (Age≤ 14 years) who underwent allogeneic HSCT from January 2020 to December 2021 were collected. Patients were divided into non-aGVHD group (n=55) and aGVHD group(n=40), and aGVHD group was divided into two subgroups: grade Ⅰ aGVHD(n=16) and grade Ⅱ-Ⅳ aGVHD(n=24). Receiver operating-characteristic curve (ROC) analysis was performed to predict aGVHD. Results: Before preconditioning in non-aGVHD and aGVHD groups, there was no significant difference in all lymphocyte subsets and ratio of CD4+/CD8+T cells. On day 14 post-transplantation in non-aGVHD and aGVHD groups, the percentages of T cells, CD4+T cells, CD8+T cells, activated CD4+T cells and NK cells were 53.42(31.17,73.50) and 77.09(60.35,84.72), 8.91(3.50,18.7) and 16.30(9.63,23.17), 30.48±2.53 and 43.37±3.19, 0.81(0.10,1.50) and 2.35(0.93,4.83), 30.34(18.29,55.09) and 14.91(7.23,26.27), respectively(P＜0.05). On day +14 (14 days post-transplantation), the differences in all cell subsets and the ratio of CD4+/CD8+ T cells were not statistically significant between grade I aGVHD and grade II-IV aGVHD subgroups. The percentages of CD8+T cells in grade Ⅰ aGVHD were significantly higher than in grade Ⅱ-Ⅳ aGVHD (51.01±4.94 versus 38.28±3.93, P=0.05). Area under the ROC curve (AUC) of T cells, CD4+T cells, CD8+T cells, activated CD4+T cells and NK cells were 0.7273, 0.6914, 0.6850, 0.7232 and 0.7243, and cut-off values were 67.01(0.709, 0.700), 14.69(0.709, 0.675), 46.93 (0.836, 0.525), 1.850 (0.800, 0.575) and 28.01 (0.636, 0.800), respectively. AUC of combined T cells and activated CD4+T cells was 0.7745. Conclusion: Our findings demonstrate that level of activated CD4+T cells on day +14 (post-HSCT) is a valuable biomarker for predicting aGVHD in children with TDTβ and CD8+T cells could likely be a biomarker for severe aGVHD.